(untitled) (The International Journal for Scientific Research, 2025)
This study explores the deep structure of political legitimacy as embodied in the bayʿa, not as a mere ritual or juristic formality, but as a foundational stratum in the historical and symbolic constitution of authority within the Islamic political imagination—most notably in the Moroccan case. Adopting an anthropological–constitutional approach, the article argues that the bayʿa is not an event that vanishes with time; rather, it is a structural residue that continues to shape the state’s identity despite institutional transformations. As shown through comparison with French, British, and Spanish models, the bayʿa emerges as a legitimacy-producing mechanism nourished by memory, ritual, and collective recognition, underlying major shifts in the relationship between community and political center. Within this comparative horizon, Morocco appears as an exceptional configuration: it brings together classical juridical heritage, tribal anthropology, and modern constitutional dynamics in a framework where Imārat al-Mu’minīn (the Commandership of the Faithful) functions as the symbolic fulcrum that constantly regenerates legitimacy through text, ritual, and memory. On the basis of makhzen archives and rigorous historiographical and anthropological studies (al-Tāzī, Bouzineb, Belhaddad, Berque, Montagne, Terrasse), the article shows that bayʿa in the Sahraʾ al-Maghribiyya (Moroccan Sahara) has never been a mere gesture of loyalty, but a politically operative mechanism structuring relations between Saharan tribal confederations and the ʿAlawid center since at least the seventeenth century. This historical continuity receives juridical confirmation in the 1975 Advisory Opinion of the International Court of Justice, which recognized the existence of “ties of allegiance” between the Sultans of Morocco and various Saharan tribes—an acknowledgment that reinforces the historical and legal embeddedness of the Moroccan Sahara within the Moroccan state. The study concludes that the bayʿa, in its broader conceptual horizon, is neither a purely religious rite nor an administrative procedure. It functions as a foundational political myth through which the state re-articulates its own self-understanding whenever historical conditions or governance structures shift. Morocco thus offers one of the clearest contemporary embodiments of this dynamic: the bayʿa operates as an extra-constitutional layer of legitimacy that sustains political cohesion and grants authority a symbolic depth bridging history, institutions, and collective memory—both in the national center and in the Moroccan Sahara.